W poszukiwaniu tego, co Inne. Współczesne reportaże podróżnicze jako opowieści o Inności - Paszek, Karolina (Dydaktyka Polonistyczna, 2020)
The article focuses on contemporary travel reportage represented by Martyna Wojciechowska,Tomek Michniewicz and Przemek Kossakowski. The texts selected by the author for analysis tellabout the unknown. The author of the article puts forward the thesis that modern travel reports arestories about multidimensional otherness. Article also includes a typology of ways of talking aboutthe phenomenon of dissimilarity. Author distinguishes three types of relating to unknown, which arerepresented by the authors of reports selected for the analysis. It is an emotional, exploratory, andspiritual type.